RESEARCH BASED WRITING AS A TECHNIQUE IN WRITING A REPORT TEXT TO SENIOR HIGH SCHOOL - Ivony Septia Ningsih; Rusdi Noor Rosa (Universitas Negeri Padang, 2013)
iiThis paper is written to describe Research Based Writing as a technique to improve students’ ability in writing a report text. It is required the students to be an active learner by gathering and developing information as ideas to write a report text. There are some steps in using Research Based Writing; first, the teacher starts to build students’ background knowledge about report text in pre teaching. Second, the teacher introduces the method that is going to be used and explains how to apply this method to help the students in writing a report text then asks the students to sit in group, give a research sheet to each group as a guideline to find and develop information about an object that is going to be reported. In this whilst teaching activity, the students also discuss with their own group to collect and arrange the ideas based on research sheet to write a report text. The last, in post teaching activity, the teacher summarize the material that has been learned. Abstrak Makalah ini bertujuan untuk menjelaskan penggunaan Research Based Writing sebagai teknik untuk meningkatkan kemampuan siswa dalam menulis teks report dengan cara siswa dituntut untuk berperan secara aktif mengumpulkan dan mengembangkan informasi dari berbagai sumber sebagai ide untuk menulis teks report. Langkah - langkah dalam menggunakan Research Based writing ini adalah dimulai dengan membangun latar belakang pengetahuan siswa terhadap teks report(Pre teaching). Guru memperkenalkan teknik yang akan digunakan serta menjelaskan bagaimana menggunakan teknik tersebut untuk membuat sebuah teks report. menyuruh siswa duduk berkelompok, memberikan research sheets kepada siswa sebagai panduan untuk mencari dan mengembangkan informasi terhadap objek yang akan dilaporkan. siswa berdiskusi dengan kelompok untuk mengumpulkan dan menyusun ide berdasarkan research sheet untuk membuat teks report(Whilst Teaching).Pada Post Teaching, guru menyimpulkan materi yang telah dipelajari.